Perspectives of HIV specialists and cardiologists on the specialty referral process for people living with HIV: a qualitative descriptive study - Charles Muiruri; Amy Corneli; Linda Cooper; Carrie Dombeck; Shamea Gray; Chris T. Longenecker; Eric G. Meissner; Nwora Lance Okeke; April C. Pettit; Teresa Swezey; Joseph Vicini; Gerald S. Bloomfield (BMC, 2022)
Abstract Background Cardiology care may be beneficial for risk factor management in people living with HIV (PLWH), yet limited information is available about the referral process from the perspectives of HIV specialists and cardiologists. Methods We conducted 28 qualitative interviews at academic medical centers in the United States from December 2019 to February 2020 using components of the Specialty Referral Process Framework: referral decision, entry into referral care, and care integration. We analyzed the data using applied thematic analysis. Results Reasons for cardiology referral most commonly included secondary prevention, uncontrolled risk factors, cardiac symptoms, and medication management. Facilitators in the referral process included ease of referral, personal relationships between HIV specialists and cardiologists, and close proximity of the clinic to the patient's home. Barriers included lack of transportation, transportation costs, insurance coverage gaps, stigma, and patient reluctance. Conclusions Our results will inform future studies on implementation strategies aimed at improving the specialty referral process for PLWH. Trial Registration ClinicalTrials.gov Identifier: NCT04025125 .